Is zakat fund collected investible? - Awang, Abdul Bari; Mhd. Sarif, Suhaimi; Ismail, Yusof (2010)
Zakat being the fifth pillar of Islam tends to be discussed among the Muslims from the general collection and distribution aspects. The collection and disbursement functions of zakat appear to be straight forward cases. As with any funds, the zakat fund will naturally accumulate as a result of payments from eligible Muslims, and after disbursement, the fund should naturally decline. If the function of zakat is receipts and disbursements, then increases due to hibah from the financial institution with which the fund is maintained will only be incidental, and perhaps, unavoidable. There is one immediate and practical issue that will confront the management of zakat collection and disbursement. Should the surplus fund be left idle, or invested to further increase wealth? The answers may be referred to in authoritative literature. There are two objectives of the study: (1) to give guidelines on the issue of investability of zakat fund based on the views of the proponents and opponents from among the ulama’ (Muslim and Islamic religious scholars) in the literature. The study obtained views from Islamic jurisprudence tertiary students (n=33) about the issue through a short survey. The results indicated that while majority of respondents agreed to allow zakat surplus to be invested for the benefits of the zakat recipients; some respondents insisted zakat fund, must be distributed to zakat qualified recipients only, regardless of the benefits and advantages. They worried that the zakat authority could not follow the conditions when it investing zakat surplus. For future research, the study suggests to interview contemporary Muslim scholars and zakat practitioners to search for alternatives for zakat surplus investment.